Analisis Penerapan Konsep Wisata Halal di Destinasi Wisata, Studi: Farmhouse Susu Lembang - Hilmi Tsania, Najwa; Ikbal, Muhamad; Sumartini, Sumartini; Zharfa, Dinda Ayu; Noor, Any Ariani (STIEPAR YAPARI Bandung, 2023)
The trend of halal tourism is increasing and attracting public interest due to the growth of the halal industry. Halal tourism includes tourism activities and attractions that adhere to the principles of Islamic law. Bandung City has destinations that fulfill the concept of halal tourism, although knowledge about this concept is still limited among the public. This study aims to identify and analyze the application of halal tourism at the Farmhouse Susu Lembang destination. Quantitative method with a descriptive approach, involving tourists who use facilities at Farmhouse Susu Lembang as the research population. The results showed that Farmhouse Susu Lembang has implemented the concept of halal tourism in accordance with the availability of facilities that support Islamic principles and meet the needs of Muslim tourists. This shows the commitment of Farmhouse Susu Lembang in providing a tourist experience that is in accordance with the principles of halal tourism.